2022
DOI: 10.3390/molecules27113643
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization and In-Vitro Antioxidant and Immunomodulatory Activities of Polysaccharide Fractions Isolated from Artemisia annua L.

Abstract: Arimisia annua L. is an important anticancer herb used in traditional Chinese medicine. The molecular basis underpinning the anticancer activity is complex and not fully understood, but the herbal polysaccharides, broadly recognised as having immunomodulatory, antioxidant and anticancer activities, are potential key active agents. To examine the functions of polysaccharides from A. annua, their immunomodulatory and antioxidant potentials were evaluated, as well as their structural characterization. The water-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 42 publications
(101 reference statements)
2
20
0
Order By: Relevance
“…2), 115 in addition to neutral or acidic branched hetero-polysaccharides. [160][161][162] In the former category, (E)-melilotoside possesses very weak growth inhibitory activity against P. falciparum asexual blood stages in vitro. 163 The existence of related compounds in A. afra remains speculative.…”
Section: Miscellaneous Compoundsmentioning
confidence: 99%
“…2), 115 in addition to neutral or acidic branched hetero-polysaccharides. [160][161][162] In the former category, (E)-melilotoside possesses very weak growth inhibitory activity against P. falciparum asexual blood stages in vitro. 163 The existence of related compounds in A. afra remains speculative.…”
Section: Miscellaneous Compoundsmentioning
confidence: 99%
“…However, polysaccharides isolated from L. chinensis reported antioxidant and anticancer activities L.…”
Section: Resultsmentioning
confidence: 99%
“…22 However, polysaccharides isolated from L. chinensis reported antioxidant and anticancer activities. 23 L. nicotianifolia methanol extract of the leaves reported higher antioxidant activity than roots methanol extract. 24 Cui et al examined the antioxidant activity of two L. chinensis extracts, stating that the antioxidant activity of both extracts was associated with the type and polarity of the extraction solvent.…”
Section: ■ Introductionmentioning
confidence: 82%
“…AAP was consisted of rhamnose, arabinose, galactose, glucose, mannose, galacturonic acid, and glucuronic acid, with a molar ratio of 2.93:3.75:7.44:58.47:20.87:5.49:1.07. According to the previous study, the appropriate dosage of AAP is 750 mg/kg ( Zhang, 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“…Addition of A. annua extract to Nile tilapia diets modulated the intestinal microbiota and altered the abundance of specific bacteria ( Fusobacteriaceae , Stenotrophomonas , and Clostridium ), thereby improving growth performance ( Soares et al, 2022 ). Notably, the polysaccharide, being a bioactive substance in A. annua , has been found to possess antitumor activity ( Yan et al, 2019 ), along with antioxidant and immunomodulatory properties, as confirmed by in vitro experiments ( Zhang et al, 2022a ). The stable structures and properties of polysaccharides, as macromolecular compounds, contribute to their notably high safety profile.…”
Section: Introductionmentioning
confidence: 92%